Colombia : Social Safety Net Assessment - World Bank (Washington, DC, 2013)
The recent economic shock provided an incentive for carrying out the analysis of Colombia's safety net of national social assistance. Even though economic growth recovered modestly in 2000, poverty and unemployment remain high, and there has been a decline in some human development indicators. This is partly due to Colombia not having an effective safety net in place, capable to address the social consequences of the crisis. These deficiencies led to the introduction in 2000 of the Red de Apoyo Social (RAS), i.e., Social Support Network. This assessment identifies issues, and recommends options for reform of the social safety net. The country is undergoing an unprecedented economic contraction, and severe fiscal imbalance that will require major reforms, notably to the pension program, before achieving macroeconomic stabilization. Therefore, the report takes into account the complex, and changing socioeconomic conditions, exacerbated by the protracted internal conflict. Such situation calls for supporting institutional viability, building on Colombia's strengths in the social sectors. Social assistance was not included in the social sector reforms for the 1990s, and the lack of strategic safety net is underscored by the fragmentation of programs within institutions, and overlapping program objectives across institutions. Targeted technical reforms should address budgeting, monitoring and evaluation to orient social assistance programs; existing programs reformed to improve quality and coverage; and, longer-term strategic reforms should focus on improving the operation of social safety nets, based on national debate, consensus, and political will.